United, Yet Apart? A Note on Persistent Labour Market Differences between Western and Eastern Germany - Claus Schnabel (Institute for the Study of Labor (IZA), 2015)
Comparing aggregate statistics and surveying selected empirical studies, this paper shows that the characteristics and results of labour markets in eastern and western Germany have become quite similar in some respects but still differ markedly in others even 25 years after unification. Whereas no substantial differences can be detected in firms' labour demand decisions and in employees' representation via works councils or trade unions, both parts of the country are somewhat apart concerning labour supply behaviour, labour productivity, wages, and bargaining coverage, and they still exhibit substantially different rates of unemployment. These differences may reflect observable and unobservable characteristics of economic actors as well as differences in behaviour, norms, and individuals' attitudes.
Keywords: J01; J20; J30; J50; P27; 330; labour market disparities; German unification; transition; Germany